The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.18196/ijnp.1149
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Benson Relaxation Technique With Anxiety In Hemodyalisis Patients In Yogyakarta

Abstract: Hemodialysis is a treatment that must be done by patients with chronic renal failure. Hemodialysis can changes the various aspects of life of patients, and it cause anxiety. One of the method that can used to reduce anxiety is Benson relaxation techniques. This technique is a combination of relaxation and elements of religious beliefs espoused. To determine the effect of Benson relaxation techniques for anxiety in patients undergoing hemodialysis therapy. Quasi Experiment pre post test design with comparison g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
(1 reference statement)
0
3
1
2
Order By: Relevance
“…This result may be explained by the Benson's technique is simple, safe technique, effective, in expensive and easy to learn by patients, and do not need any equipment or resources. On opposite side a study done in Yogyakarta by Kurniasari, 2016 who reported that Benson's relaxation technique have no effect on anxiety scores of hemodialysis patients (42) .This contradiction may be explained by this paper apply Benson's relaxation for a period of two weeks only and this period was not enough to decrease the level of anxiety while our study conducted for two months.…”
Section: Discussioncontrasting
confidence: 54%
“…This result may be explained by the Benson's technique is simple, safe technique, effective, in expensive and easy to learn by patients, and do not need any equipment or resources. On opposite side a study done in Yogyakarta by Kurniasari, 2016 who reported that Benson's relaxation technique have no effect on anxiety scores of hemodialysis patients (42) .This contradiction may be explained by this paper apply Benson's relaxation for a period of two weeks only and this period was not enough to decrease the level of anxiety while our study conducted for two months.…”
Section: Discussioncontrasting
confidence: 54%
“…It does not match (Nuri Kurniasari et al, 2016)that the value of pretest and posttest anxiety in the two groups, namely the intervention group and the comparison group, decreased, namely moderate anxiety to mild anxiety. In addition, the two data did not show a significant difference between the intervention and comparison groups.…”
mentioning
confidence: 83%
“…(Morita et al, 2020). In addition, the Benson relaxation technique can also improve the patient's sleep quality (Nuri Kurniasari et al, 2016). Benson relaxation therapy usually takes only 10-20 minutes even under any conditions and has no impact on the patient (Anisah & Maliya, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Otaghi et al (2016) mengemukakan bahwa relaksasi Benson melibatkan teknik mindfulness yang mempengaruhi fisik dan psikologis. Teknik relaksasi Benson adalah pengembangan metode relaksasi pernapasan yang melibatkan faktor keyakinan pasien, berfokus pada kata tertentu atau kalimat yang diucapkan secara berulang dengan ritme yang teratur (Kurniasari et al, 2016). Rahman et al (2019) mengemukakan bahwa relaksasi Benson adalah terapi religius yang dalam pelaksanaannya melibatkan faktor keyakinan agama.…”
Section: Pendahuluanunclassified